2005
DOI: 10.4049/jimmunol.174.12.7592
|View full text |Cite
|
Sign up to set email alerts
|

TCR Engagement Increases Hypoxia-Inducible Factor-1α Protein Synthesis via Rapamycin-Sensitive Pathway under Hypoxic Conditions in Human Peripheral T Cells

Abstract: Peripheral T cells encounter rapid decrease in oxygen tension because they are activated by Ag recognition and migrate into inflammatory sites or tumors. Activated T cells, therefore, are thought to have such machineries that enable them to adapt to hypoxic conditions and execute immune regulation in situ. We have recently shown that survival of CD3-engaged human peripheral blood T cells is prolonged under hypoxic conditions and hypoxia-inducible factor-1 (HIF-1) and its target gene product adrenomedullin play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
117
3
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(126 citation statements)
references
References 37 publications
4
117
3
1
Order By: Relevance
“…Hypoxia inducible factor controls the expression levels of several essential genes that are required for cell and tissue adaptation to hypoxia including glucose transporters, glycolytic enzymes, vascular endothelial cell growth factor, NO synthase, and erythropoietin (55,56). T cell activation also up-regulates glucose transporters and glycolytic enzymes (57), perhaps to prepare the cells for entry into hypoxic environments.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia inducible factor controls the expression levels of several essential genes that are required for cell and tissue adaptation to hypoxia including glucose transporters, glycolytic enzymes, vascular endothelial cell growth factor, NO synthase, and erythropoietin (55,56). T cell activation also up-regulates glucose transporters and glycolytic enzymes (57), perhaps to prepare the cells for entry into hypoxic environments.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor hypoxia-inducible factor 1α (HIF1α) is positively regulated by PI3K-AKT-mTOR signals 101,102 . HIF1α induces the expression of genes that are required for glycolysis when stabilized by low oxygen availability.…”
Section: Box 2 | Phenotypic Plasticity In Inflammatory and Regulatorymentioning
confidence: 99%
“…HIF-1␣ expression in T lymphocytes can be induced both by hypoxia (16) and by non-hypoxic pathways, including TCRtriggered and PI3K-mediated pathways, resulting in mRNA up-regulation and protein stabilization (17)(18)(19). We previously demonstrated that T cell activation leads to "immediate early response gene" up-regulation of the alternative mRNA isoform of HIF-1␣ I.1 (20), which contains a different first exon and is expressed from self promoter in a immune tissue-specific manner (21,22).…”
mentioning
confidence: 99%